(untitled) (Jurnal Matematika, Statistika dan Komputasi, 2025)
A stock portfolio is a combination of two or more equity securities invested over a specific period and under certain conditions. This research analyzes stock combinations that can be formed into an optimal portfolio using the Markowitz method. The Markowitz method is employed to maximize returns and minimize the risk of a portfolio. The data used in this study consists of daily closing prices from the IDX-MES BUMN17 index, one of the indices in Indonesian Stock Exchange, between January 2023 and December 2023. Based on the results obtained, two recommended portfolios are identified, known as the Minimum Variance Portfolio (MVP) and Tangency Portfolio. The optimal portfolio can serve as an option depending on the investor’s risk profile.